Negotiating Identity: The Cultural and Religious Significance of Rifa'iyah Batik for Women - Sigit Setyawan; Titis Srimuda Pitana; Prasetyo Adi Wisnu Wibowo (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
This study examines how the Rifa'iyah batik tradition becomes a conveyance for self-actualization for Rifa'iyah women in public spaces, focusing on negotiating women's identity in existing social constructions. Located in Kalipucang Wetan, Batang, Jawa Tengah Indonesia. This study uses a descriptive qualitative method with a post-structuralist feminist approach to reveal the dynamics of Rifa'iyah women's identity. Data were obtained through interviews with batik artisans and cultural observers, observations, and literature studies. The study results show that Rifa'iyah women can negotiate sociocultural structures through the batik tradition, changing society's perception of the role of women in the public sphere. They are not merely economic actors who contribute to family income but also agents of social change and cultural preservers. The gender identity of Rifa'iyah women is proven to be dynamic and continues to be formed through repeated actions and negotiations with prevailing norms. The implications of this study enrich cultural and gender studies, especially in understanding the interaction between gender, spirituality, and culture in shaping women's identity. This study also provides a new perspective on how women can utilize creative spaces to participate in the public sphere without violating the values ​​​​adopted by society. Research findings are relevant to women's empowerment efforts in traditional societies, showing that traditions can empower when interpreted and practised creatively.